A relação entre a capacidade de absorção e inovação aberta: Um estudo de caso no setor turístico do município de Prudentópolis – PR - Souza, Lucas Batista de (2020)
This study addresses the relationship between the absorption capacity of organizations for the generation of innovations originated through external sources of knowledge. We sought to identify what the sources are and how knowledge exchange occurs in the organizations studied; To investigate how the five dimensions of the absorption capacity process (recognition of value, acquisition, assimilation, transformation and exploration) happen in the studied context; Describe how the flow of external knowledge occurs in the companies / institutions studied, in order to generate open innovations, in addition to checking for possible gaps and suggesting improvements in the process of capacity for absorbing knowledge through external sources and the generation of open innovations in the sector studied. To this end, the chosen field was the tourism sector of the municipality of Prudentópolis - PR, with independent professionals, managers and owners of companies in the segment formally constituted and qualified in CADASTUR being interviewed. In the methodology, qualitative research of a descriptive and analytical nature and multiple case studies were used as a research strategy. The results of the study were the identification and exposure of the role of each of the sources of external knowledge in the field, demonstrating how each dimension of absorption (recognition of value, acquisition, assimilation, transformation and exploration) occurs in the context studied for the generation open innovations, also checking gaps and suggesting improvements in the ACAP process. Still, the results showed distinct relationships between each source of knowledge and company, varying in the level of recognition, degree of similarity with internal knowledge and receptivity with the team. As for the dimensions of ACAP, there was a low frequency of attempts by the organizations studied to seek to acquire knowledge, being carried out in most cases in a non-systematic and informal way, demonstrating the dimension “absorption” as the main bottleneck in the described process. As for assimilation, knowledge is easily related to internal knowledge by the organization and its team, being close to the knowledge already established and the incorporation of exported knowledge related to the individual characteristics of the team members and not to the collective. Finally, the perceived results of the process demonstrated a large amount of incremental open innovation generation, establishing that the ACAP process generates new opportunities for these companies.